Video games and their associations with physical health: a scoping review. Issue 1 (2nd October 2020) - Huard Pelletier, Vincent; Lessard, Arianne; Piché, Florence; Tétreau, Charles; Descarreaux, Martin
Abstract : Objective: The objective of this scoping review is to investigate the possible links between the practice of video games and physical health. It seeks to answer the following question: What are the physical health consequences of playing video games in healthy video game player? and How is it currently investigated?. Methods: A scoping review was conducted to identify observational and experimental studies pertaining to our research question. Retrieved papers were screened using a two-phase method first involving a selection based on titles and abstracts. Then, potentially relevant studies were read and triaged. The final set of included studies was analysed, and data were subsequently extracted. Observational studies and experimental studies were assessed using the appropriate Cochrane Risk of Bias Tool and data were synthetised according to specific physical health and related health behaviours. Results: Twelve peer-reviewed articles were retained for further analyses. Results of this scoping review suggest preliminary evidence that time spent gaming is associated with some health outcomes indicators. Our results indicate preliminary evidence that increased gaming time is associated with higher body mass index and lower self-reported general health status. There is insufficient evidence to conclude on a possible association between gaming time and physical activity or sedentary behaviours, sleep or fatigue, musculoskeletal pain or dietary behaviours. Conclusion: The results of this sopping review suggest an association between increased video game playing time and a deterioration in some physical health indicators but available evidence is scarce, precluding from any strong conclusion.